Desarrollo de una lista de verificación de los requisitos legales establecidos en la norma NTC-ISO/IEC 17024:2013 (2015)
Colombia currently has a growth in the productive sector which requires specific labor skills to carry out safe work, which must be legitimized by Certifying Bodies of Persons that must be accredited by the National Accreditation Body of Colombia (ONAC), but due to ignorance of the requirements and guidelines with which these Organisms must comply, a number of damages to third parties have been generated due to liability issues. In addition to the above, the need to legally certify the labor competencies of the people, and the ignorance of the International Standard and current Colombian regulations applied to their activities, arose the need to carry out this degree project, which was developed through the following stages : Identification of all the requirements contained in NTC ISO / IEC 17024: 2013 giving greater relevance to those containing the legal aspects for purposes of compliance with the legislation, then proceeded to perform the analysis of each legal requirement according to the regulations existing and finally a checklist was constructed, which serves as a guide for natural or legal persons that intend to conform and be accredited to the ONAC to certify people. This checklist contains all the documents that are required to comply with the legal regulations and therefore the requirements of NTC ISO / IEC 17024: 2013 and serves as an application tool, which helps to focus on legal matters to people who want to certify people.